2004
DOI: 10.2165/00129784-200404010-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Use ???of Vitamin K in Patients on Anticoagulant Therapy

Abstract: Anticoagulation with antivitamin K (AVK) is very effective for primary and secondary prevention of thromboembolic events. However, questions persist about the risks and management of over-anticoagulation. For reversal of excessive anticoagulation by warfarin, AVK withdrawal, oral or parenteral vitamin K administration, prothrombin complex or fresh frozen plasma may be used, depending on the excess of anticoagulation, the existence and site of active bleeding, patient characteristics and the indication for AVK.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 61 publications
0
23
0
3
Order By: Relevance
“…The oral anticoagulant preferred for the outof-hospital anticoagulation was the AVK acenocumarol, an old drug and less costly option for PTE patients from Romania [21]. LMWH at discharge 242 was prescribed to 4 patients with active cancer as recommended by the current guideline.…”
Section: Discussionmentioning
confidence: 99%
“…The oral anticoagulant preferred for the outof-hospital anticoagulation was the AVK acenocumarol, an old drug and less costly option for PTE patients from Romania [21]. LMWH at discharge 242 was prescribed to 4 patients with active cancer as recommended by the current guideline.…”
Section: Discussionmentioning
confidence: 99%
“…16) Hanslik, et al confirmed that the use of vitamin K in patients with warfarin over-anticoagulation lowers excessively elevated INR faster than withholding warfarin alone. 17) Willms, et al found that low-intensity warfarin (INR 1.5-2.1) was safe and effective to reduce the likelihood of major hemorrhagic or ischemic events in patients with non-valvular AF during the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 A vitamina K pode ser administrada por via intravenosa (IV), subcutânea (SC), intramuscular (IM) ou oral (VO). 3,6,7 A administração por via oral da vitamina K é efetiva e tem, como vantagem, ser mais segura e conveniente que a via parenteral. 7 No Brasil, estão disponíveis, atualmente, apenas apresentações por via parenteral da vitamina K em monoterapia, sendo que o Kanakion® MM solução injetável 2mg/0,2mL é a única apresentação registrada que permite o uso por via oral, além do uso por via intravenosa e intramuscular.…”
Section: Introductionunclassified
“…3,6,7 A administração por via oral da vitamina K é efetiva e tem, como vantagem, ser mais segura e conveniente que a via parenteral. 7 No Brasil, estão disponíveis, atualmente, apenas apresentações por via parenteral da vitamina K em monoterapia, sendo que o Kanakion® MM solução injetável 2mg/0,2mL é a única apresentação registrada que permite o uso por via oral, além do uso por via intravenosa e intramuscular. Todas as outras apresentações disponíveis no mercado (Eskavit®, Kavit®, Vikatron®, Vita K®, Menadion®) são de uso por via intramuscular, intravenoso ou subcutâ-neo, não constando em bula qualquer informação quanto ao uso oral dessas apresentações.…”
Section: Introductionunclassified